2018
DOI: 10.1111/crj.12774
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan therapy for pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension: A systemic review and meta‐analysis

Abstract: Bosentan is effective in treating PAH, whereas it improves only certain hemodynamic parameters of CTEPH. Incidence of liver function abnormality is higher in bosentan treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Firstly, for bosentan, one meta-analysis including 10 RCTs showed that bosentan reduced mPAP by 5.7 mmHg, increased CI by 0.4 L/minute/m 2 , and reduced PVR by 305.1 dyne s/cm 5 as compared with placebo. 13) Secondly, for ambrisentan, the result of the ATHENA-1 trial which evaluated the safety and efficacy of sequential add-on therapy of ambrisentan to 33 PAH patients who remained symptomatic despite background phosphodiesterase 5inhibitor (PDE5-I) monotherapy, indicated that ambrisentan achieved significant improvements in mPAP, CI, and PVR, the mean changes of which from baseline were −5.4 mmHg, +0.58 L/minute/m 2 , and −249 dyne s/cm 5 , respectively, after 6 months. 14) Thirdly, for macitentan, the results of the SERAPHIN hemodynamic substudy, which evaluated the hemodynamic efficacy of macitentan as compared with placebo in PAH patients, demonstrated that macitentan 10 mg achieved significant improvement of mPAP, CI, and PVR in 57 PAH patients after 6 months, the mean changes of which from baseline were −5.3 mmHg, +0.3 L/minute/m 2 , and −274 dyne s/cm 5 , respec- tively, and mean treatment effects of which as compared with placebo were −6.4 mmHg, +0.63 L/minute/m 2 , and −416 dyne s/cm 5 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, for bosentan, one meta-analysis including 10 RCTs showed that bosentan reduced mPAP by 5.7 mmHg, increased CI by 0.4 L/minute/m 2 , and reduced PVR by 305.1 dyne s/cm 5 as compared with placebo. 13) Secondly, for ambrisentan, the result of the ATHENA-1 trial which evaluated the safety and efficacy of sequential add-on therapy of ambrisentan to 33 PAH patients who remained symptomatic despite background phosphodiesterase 5inhibitor (PDE5-I) monotherapy, indicated that ambrisentan achieved significant improvements in mPAP, CI, and PVR, the mean changes of which from baseline were −5.4 mmHg, +0.58 L/minute/m 2 , and −249 dyne s/cm 5 , respectively, after 6 months. 14) Thirdly, for macitentan, the results of the SERAPHIN hemodynamic substudy, which evaluated the hemodynamic efficacy of macitentan as compared with placebo in PAH patients, demonstrated that macitentan 10 mg achieved significant improvement of mPAP, CI, and PVR in 57 PAH patients after 6 months, the mean changes of which from baseline were −5.3 mmHg, +0.3 L/minute/m 2 , and −274 dyne s/cm 5 , respec- tively, and mean treatment effects of which as compared with placebo were −6.4 mmHg, +0.63 L/minute/m 2 , and −416 dyne s/cm 5 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although PDE5i and ETRA demonstrated haemodynamic improvement in CTEPH, 34 some patients did not achieve satisfactory management, whereas others developed side effects. 35,36 Although riociguat is the only therapy approved by the Food and Drug Administration for CTEPH, it has not yet been approved in China. As a result, PDE5i and ETRA are still used in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…It is an antagonist of both ET A and ET B , however, its affinity to ET A is approximately 100 times greater than for the ET B [6] . Bosentan is proven to reduce pulmonary arterial pressure and arterial vessels resistance, increase cardiac output and improve performance of patients with PAH [13] , [14] . Moreover, it has been reported that bosentan is effective in treatment of ARDS [15] , [16] .…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%